Medication-overuse headache: a narrative review - Helin Gosalia; David Moreno-Ajona; Peter J. Goadsby (The Journal of Headache and Pain, 2024)
Abstract Medication-overuse headache (MOH), which potentially involves 1–2% of the population, is defined as a headache, on ≥ 15 days a month affected, along with overuse of one or other acute attack medications. MOH presents with significant challenges in the headache community, particularly in clinical settings raising various questions about its pathophysiology. Through a review of the current literature and our clinical experience, we have explored the mechanisms through which MOH may occur, provide an understanding of the current state of treatment and detail some possible views on the understanding and treatment of this condition. We evaluate the variations in treatment methods offered globally and understanding of the disorder. Above all interventions, patient education is crucial, which is underscored by an analysis of the academic publications. Given the condition is preventable, early intervention is imperative and patient awareness is highlighted as key. Globally, there is no uniform treatment methodology, which may be advantageous as approaches need to take local circumstances into account.